Penguatan Kompetensi Guru MGMP Seni Budaya SMP melalui Pelatihan Koreografi di Kabupaten Takalar - Rahma M; Bau Salawati; Andi Baetal Mukadas; R. Mekar Liza Ramadhina; Lulu Afifah Ichsan (Sureq: Jurnal Pengabdian Masyarakat Berbasis Seni dan Desain, 2026)
This community service activity aims to strengthen the competencies of junior high school (SMP) Arts and Culture teachers who are members of the MGMP in Takalar Regency through choreography training. This program was motivated by teachers’ limited understanding and skills in teaching choreography effectively. The implementation method employed a workshop approach consisting of interactive lectures, demonstrations, hands-on practice, and mentoring with evaluation. The results indicate an improvement in both theoretical and practical competencies of teachers in understanding basic choreography elements (space, time, and energy), developing movement motifs, and composing simple dance works. Participants also showed high enthusiasm and readiness to apply the training outcomes in classroom learning. This activity contributes to improving the quality of arts education that is more creative, contextual, and student-centered.